Ateji Meaning on Manga ‘Majo no Kaigashuu’「魔女の怪画集」 - Gunawan, Shafiranisa Putri; Yuniarsih, Yuniarsih; Setiawati, Nia (Chi e Journal of Japanese Learning and Teaching, 2024)
This study examines the meaning of ateji in the manga Majo no Kaigashuu by Hachi. Japanese writing often highlights language's dynamic and arbitrary nature, as seen in kanji readings (furigana) that deviate from standard usage, known as ateji. Due to this arbitrary nature, the intended meaning of ateji can sometimes be obscured, even though its purpose is often to enhance word meanings. This research seeks to clarify the meanings of ateji in the text to capture the author’s intent and minimize misinterpretation. A qualitative descriptive method is employed to analyze data by types and relationships, using Shirose's (2012) categorization of ateji and Sutedi's (2019) framework for semantic relationships and shifts. The findings reveal 26 instances of ateji, grouped into seven categories. These instances suggest that ateji conveys layered meaning, emphasises certain words, and specifies subjects. The semantic relationships include synonymy, hyponymy-hypernymy, and homonymy. Additionally, this study found alternative ateji readings where meanings remained consistent despite different kanji interpretations.